Residents of the Cities in the Levant - Lababneh, Adnan Ahmed Mohammed (Journal of Posthumanism, 2025)
Since the Umayyads took over the rule of the Levant, the reconstruction of the region began during their era, the term "reconstruction," according to Ibn Khaldun, means that people settled in one place, and the ultimate goal of urbanization is civilization, followed by the build of a state, where the Umayyads replaced the nomadic lifestyle with urban living. The Levant, as a geographical area of civilization, possesses the elements necessary for life, previous civilizations, such as the Arameans, Phoenicians, Hellenistic, and Roman, thrived there, each contributing its own architectural and cultural characteristics. The prosperity of the cities in the Levant throughout its long history can be attributed to a combination of economic and commercial factors that played a significant role in the emergence of both inland and coastal trade cities, due to the abundance of agricultural land, rainfall, and river waters. With the arrival of Muslims in the Levant, urban development flourished, transforming ancient cities into Islamic ones. Mosques, governor's houses, and walls were constructed to ensure their security and political stability. The Umayyads also established new cities out of necessity and civilizational advancement, such as Ramla and Rusafa. The predominant characteristic of these new cities was their military necessity, along with economic benefits. The Roman city necessarily included a fortress due to its military nature, but Breneh argues that a city should also have commercial centers, markets, and trade routes. Greenbaum described a city as having political authority, markets, geographical boundaries, and a council of residents. The Arab city was distinguished by its mosque, markets, governor's house, walls, and palaces. Massignon noted that Islamic cities relied on key elements, primarily financial institutions, money changers, and commercial shops (qaysariyya). Some Islamic cities were built on a tribal basis, as the foundation of society was tribal. The Arabs were not new to urban life; Mecca and Medina were already established commercial and religious cities before Islam. With the Islamic conquests, Muslims built cities in Egypt and Iraq, so it was not strange for Arabs to inhabit or develop cities. Thus, Arabs populated most of the regions and lands they entered, spreading civilization and urban life in industry, agriculture, and trade. The conquering Muslims were the first to transform the Levant into cities and military camps, moving their dwellings from tents to houses. Omar bin Al-Khattab ordered the people to settle in cities like Damascus, Aleppo, and Hama, which during the Umayyad period had mosques, centers of governance, administration, and markets. After the Muslims settled, they added a number of modern cities such as Ramla and Rusafa, which were built by Hisham bin Abdul Malik. What is important to us here is that the Arab Islamic conquests were a factor in the ever-developing civil and urban construction, such that they were able to create advanced human activities in the political, economic and social fields and the emergence of civil society institutions such as housing, institutions, craft unions and others, as the Levantine cities became productive cities that provided all the necessities of life for their residents under the Umayyad rule.